Five new species of Eiphosoma Cresson, 1865 (Ichneumonidae: Cremastinae) from Colombia, new records, and a key to Colombian species - Cuéllar-Ramírez, Mauricio; Ramos-Pastrana, Yardany; Fernandes, Daniell R. R. (Zootaxa, 2023)
A taxonomic study of the species of the Darwin wasp genus Eiphosoma Cresson, 1865 (Hymenoptera: Ichneumonidae: Cremastinae) from the department of Caquetá, Colombia, resulted in five new species being described: E. caqueta sp. nov. (Type locality: Curillo, Caquetá), E. eneke sp. nov. (Type locality: San Vicente del Caguán, Caquetá) E. interpunctum sp. nov. (Type locality: Solano, Caquetá,), E. rumi sp. nov. (Type locality: Florencia, Caquetá) and E. sinecarenatum sp. nov. (Type locality: Florencia, Caquetá). With this paper, the number of Eiphosoma species from Colombia increases from three to 16. Eiphosoma bogan Gauld, 2000; E. dentator (Fabricius, 1804); E. dolopon Gauld, 2000; E. fluminense Costa Lima, 1953; E. fuzhi Gauld, 2000; E. macrum (Enderlein, 1921); E. minense Costa Lima, 1953 and E. tantalium Gauld, 2000 are recorded for the first time from Colombia. A dichotomous key to the Colombian species is presented.